2018
DOI: 10.1016/j.jmr.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of spatially-resolved displacement propagators using compressed sensing APGSTE-RARE MRI

Abstract: A method is presented for accelerating the acquisition of spatially-resolved displacement propagators via under-sampling of an Alternating Pulsed Gradient Stimulated Echo - Rapid Acquisition with Relaxation Enhancement (APGSTE-RARE) data acquisition with compressed sensing image reconstruction. The method was demonstrated with respect to the acquisition of 2D spatially-resolved displacement propagators of water flowing through a packed bed of hollow cylinders. The q,k-space was under-sampled according to varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…1. As described in our earlier work [2], the 13-interval APGSTE sequence was used for displacement (q) encoding, because it partially compensates for the effects of internal gradients that are expected to be present in many of the porous media of interest [8]. The RARE experiment was used for spatial (k) encoding.…”
Section: Apgste-rare Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. As described in our earlier work [2], the 13-interval APGSTE sequence was used for displacement (q) encoding, because it partially compensates for the effects of internal gradients that are expected to be present in many of the porous media of interest [8]. The RARE experiment was used for spatial (k) encoding.…”
Section: Apgste-rare Experimentsmentioning
confidence: 99%
“…However, direct Fourier transformation of under-sampled data leads to image artefacts due to violation of the Nyquist sampling rate. It has previously been shown that compressed sensing (CS) can be used for artefact-free recovery of magnetic resonance data [6,7] and recently, application to the measurement of a 2D spatially-resolved propagator from under-sampled q,k-data has been demonstrated [2]. In this paper the extension of this work to include a third spatial dimension is described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…oil and water), which can potentially alter the properties of the system. Although the routinely used spatial resolution of MRI is lower (a few hundred µm), it offers a range of different noninvasive contrast mechanisms, based on, for example, fluid type via the MR chemical shift (Ramskill et al ., ), wetting properties via MR relaxation time constants (Reci et al ., ), and fluid mobility via MR measurements of molecular self‐diffusivity, flow dispersion and velocity (Mitchell et al ., ; Colbourne et al ., ; de Kort et al ., , b). Thus, the high spatial resolution MRI acquisitions enabled by the present work are of particular relevance in studying structure‐flow correlations, imaging displacement processes and mapping spatial variation in fluid‐surface interactions in rocks.…”
Section: Introductionmentioning
confidence: 99%
“…The main principle of CS is that it is possible, with a high probability, to reconstruct a signal from far fewer samples than is required by the classical sampling theory [33,34], provided the sampling is done randomly and the signal is sparse in some domain. Using CS, it has become possible, for example, to rapidly image single-phase [35,36] and multi-phase [37] displacement processes in rock core floods using 3D MRI.…”
Section: Introductionmentioning
confidence: 99%